2022
DOI: 10.2147/amep.s368519
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Medical Students’ and Interns’ Knowledge and Perception of Artificial Intelligence in Medicine

Abstract: Artificial intelligence (AI) is playing an increasingly important role in healthcare and health professions education. This study explored medical students' and interns' knowledge of artificial intelligence (AI), perceptions of the role of AI in medicine, and preferences around the teaching of AI competencies. Methods: In this cross-sectional study, the authors used a previously validated Canadian questionnaire and gathered responses from students and interns at KIST Medical College, Nepal. Face validity and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 32 publications
5
15
0
Order By: Relevance
“…Questions related to knowledge were of AI were graded on a 3-point Likert scale. and technicians, regarding AI and its applications [12]. However, most of our participants did not have any formal AI training in their education or careers, which aligns with a similar study from India [13] and Nepal [14].…”
Section: Methodssupporting
confidence: 80%
“…Questions related to knowledge were of AI were graded on a 3-point Likert scale. and technicians, regarding AI and its applications [12]. However, most of our participants did not have any formal AI training in their education or careers, which aligns with a similar study from India [13] and Nepal [14].…”
Section: Methodssupporting
confidence: 80%
“…This was however similar to other research done in developing countries. A study in Nepal found about half of the students did not understand the term ''Arti cial Intelligence'' [19]. These ndings can be seen hand in hand to the fact that the medical curriculum in most developing countries including Ethiopia and Nepal do not include Arti cial Intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, study conducted by Saad et al reported that only 18.4% of students had taken AI courses, and these students were more likely to emphasize the signi cant role of AI in healthcare [16]. Likewise, a study conducted by Jha et al showed that 91.7% of participants did not attend AI courses, and 95.8% were not involved in programming courses either [25]. These variations highlight signi cant differences in the exposure to AI courses and programming language learning between our study sample and previous research, underscore potential variations in educational backgrounds or interests among the participants, which could imply disparities in their learning experiences [24].…”
Section: Discussionmentioning
confidence: 99%